The Future of the Global Economy in the Light of Inflationary and Deflationary Trends and Long Cycles Theory. Issue 2 (17th February 2018) - Grinin, Leonid E.; Korotayev, Andrey V.
Abstract : Recent years and months have evidenced an increase in deflationary phenomena. The present article defines the reasons for the problem, explains the irregularity of the inflation–deflation processes in the world and forecasts on this basis that the crisis-depressive phase of development in the global economy will continue for a relatively long time. Based on an analysis of available resources and the theory of long cycles, we believe that in the next 5–10 years, the global economy will continue being in the crisis-depression phase with rather sluggish and weak rises. The article also offers some forecasts for the forthcoming sixth Kondratieff wave (2020–the 2060/70s), identifies its possible technological basis, and discusses possible consequences of the forthcoming technological transformations.